Hierarchical N- and O-Doped Porous Carbon Composites for High-Performance Supercapacitors. (27th June 2018) - Zou, Ben-Xue; Wang, Yan; Huang, Xiaodong; Lu, Yanhua
Abstract : Hierarchical N- and O-doped porous carbon composites were prepared by hydrothermally assembling of silk fibers with low molecular weight phenolic resin, followed by carbonization and KOH activation process. Silk fibroin is expected to provide nitrogen and oxygen functionalities for the final composite carbon. The introduction of thin layer graphitic structures of low molecular weight phenolic resin-derived carbon offers more abundant structures, low resistance, and hierarchical porosity with a high BET surface area of 1927 m 2 ·g −1 . The composition and electrochemical properties of the composite carbon have been studied as a function of the annealing temperature for KOH activation process. The obtained carbon composite exhibits high specific capacitance as high as 330 F·g −1 (1000 mF·cm −2 ) at 0.5 A·g −1, good rate capability, and excellent cycling stability (91% of capacitance retention after 10000 cycles) in 6 M KOH electrolyte.